Friday

March 6, 2015

March 6, 2015

Posted by **jessica** on Friday, May 3, 2013 at 9:08pm.

- college agebra -
**Reiny**, Friday, May 3, 2013 at 10:20pm(3x^2 - 2x - 1)(x^2 + x + 5)

= 3x^4 + 3x^3 + 15x^2 + -2x^3 - 2x^2 ..... etc

(you should have 9 terms in this line)

can you see what I am doing?

it is just an expanded version of the old FOIL concept

I am sure you can finish it

There will be all kinds of like terms, make sure to simplify.

compare your answer with

http://www.wolframalpha.com/input/?i=expand+%283x%5E2+-+2x+-+1%29%28x%5E2+%2B+x+%2B+5%29

**Answer this Question**

**Related Questions**

Math - The question is simply and answer in standard form 3x2(that is x squared...

math - 3xsquared + 27 = 5 3xsquared -5x = -3xsquared + 6 SOLVE

Algebra - Solve for "x" in each equation. 1)xsquared+12x+25= 0 2)xsquared+4x-12...

math(check my answers) - SOLVE THE FOLLOWING EQAUTION BY COMPLETING THE SQUARE: ...

college algebra - h(x)=3xsquared+5x-3

Algebra - Solve for y in terms of x . Determine if y is a function of x . If it ...

math check my answers - 1. 2(x+3)squared-6x+5=0 Answer= 2xsquared+6x+23=0 2. ...

Intermediate Algebra - Please help with the below. I know the answer I need help...

math - 1. 2xsquared-7x=-6 2. xsquared + 12x + 1= 0 3. xsquared + 6x + 20 = 0

algebra (parabolas) - tell whether the graph opens upward or downward. then find...